Productivity Viewed From Work Ability and Work Operation Time With Mediating Variable On The Job Training (OJT) - Gumilar, Bagja; Hariadi, Eko; Agung, Achmad Imam (Technium Social Sciences Journal, 2024)
This study aims to analyze the effect of work ability and work operational time on cadet productivity and analyze the role of the on-the-job training (OJT) variable in mediating the independent variable on the dependent variable in the Airport Electrical Engineering Occupation at Politeknik Matra Udara. Data were collected through questionnaires distributed to respondents. This research uses a quantitative approach, analyzes using Structural equation modeling (SEM), and uses the Smart-PLS statistical program. The research sample refers to the Isaac and Michael table using a 10% significance level. The sample of this study consisted of 115 cadets from various occupations in airport electrical engineering at the Air Matra Polytechnic who had participated in the on-the-job training (OJT) program. The results of the analysis show that work ability has a significant positive effect on cadet productivity. This shows that the higher a person's work ability, the higher his productivity. In addition, work-related operational time also has a positive effect on productivity. That is, the longer the working time owned by cadets, the higher the level of productivity. Furthermore, on-the-job training (OJT) proved to be a significant mediator in the relationship between work ability and work operational time and cadet productivity. This suggests that on-the-job training has an important role in improving productivity.